Lupus Anticoagulant Single Positivity During the Acute Phase of COVID‐19 Is Not Associated With Venous Thromboembolism or In‐Hospital Mortality. Issue 11 (22nd September 2021) - Gendron, Nicolas; Dragon‐Durey, Marie‐Agnès; Chocron, Richard; Darnige, Luc; Jourdi, Georges; Philippe, Aurélien; Chenevier‐Gobeaux, Camille; Hadjadj, Jérôme; Duchemin, Jérôme; Khider, Lina; Yatim, Nader; Goudot, Guillaume; et al.
Abstract : Objective: The clinical relevance of antiphospholipid antibodies (aPLs) in COVID‐19 is controversial. This study was undertaken to investigate the prevalence and prognostic value of conventional and nonconventional aPLs in patients with COVID‐19. Methods: This was a multicenter, prospective observational study in a French cohort of patients hospitalized with suspected COVID‐19. Results: Two hundred forty‐nine patients were hospitalized with suspected COVID‐19, in whom COVID‐19 was confirmed in 154 and not confirmed in 95. We found a significant increase in lupus anticoagulant (LAC) positivity among patients with COVID‐19 compared to patients without COVID‐19 (60.9% versus 23.7%; P < 0.001), while prevalence of conventional aPLs (IgG and IgM anti–β2 ‐glycoprotein I and IgG and IgM anticardiolipin isotypes) and nonconventional aPLs (IgA isotype of anticardiolipin, IgA isotype of anti‐β2 ‐glycoprotein I, IgG and IgM isotypes of anti–phosphatidylserine/prothrombin, and IgG and IgM isotypes of antiprothrombin) was low in both groups. Patients with COVID‐19 who were positive for LAC, as compared to patients with COVID‐19 who were negative for LAC, had higher levels of fibrinogen (median 6.0 gm/liter [interquartile range 5.0–7.0] versus 5.3 gm/liter [interquartile range 4.3–6.4]; P = 0.028) and C‐reactive protein (CRP) (median 115.5 mg/liter [interquartile range 66.0–204.8] versus 91.8 mg/liter [interquartile range 27.0–155.1]; P = 0.019). Univariate analysis did not show any association between LAC positivity and higher risks of venous thromboembolism (VTE) (odds ratio 1.02 [95% confidence interval 0.44–2.43], P = 0.95) or in‐hospital mortality (odds ratio 1.80 [95% confidence interval 0.70–5.05], P = 0.24). With and without adjustment for CRP level, age, and sex, Kaplan‐Meier survival curves according to LAC positivity confirmed the absence of an association with VTE or in‐hospital mortality (unadjusted P = 0.64 and P = 0.26, respectively; adjusted hazard ratio 1.13 [95% confidence interval 0.48–2.60] and 1.80 [95% confidence interval 0.67–5.01], respectively). Conclusion: Patients with COVID‐19 have an increased prevalence of LAC positivity associated with biologic markers of inflammation. However, LAC positivity at the time of hospital admission is not associated with VTE risk and/or in‐hospital mortality.